Maternal genetic polymorphisms in the major mitotic checkpoint genes MAD1L1 and MAD2L1 associated with the risk of survival in abnormal chromosomal fetuses - Chan, Ying; Liu, Yize; Kong, Yamin; Xu, Weiming; Zeng, Xiaohong; Li, Haichun; Guo, Yan; Tang, Xinhua; Zhang, Jinman; Zhu, Baosheng (Frontiers in Genetics, 2023)
Background: The genetic etiology of fetal chromosome abnormalities remains unknown, which brings about an enormous burden for patients, families, and society. The spindle assembly checkpoint (SAC) controls the normal procedure of chromosome disjunction and may take part in the process. Objective: The aim of this study was to explore the association between polymorphisms of MAD1L1 rs1801368 and MAD2L1 rs1283639804, involved in SAC and fetal chromosome abnormalities. Methods: The case–control study collected 563 cases and 813 health controls to test the genotypes of MAD1L1 rs1801368 and MAD2L1 rs1283639804 polymorphisms by polymerase chain reaction–restrictive fragment length polymorphism methods (PCR-RFLP). Results:MAD1L1 rs1801368 polymorphism was associated with fetal chromosome abnormalities alone or combined to lower homocysteine (HCY) levels (alone: dominant: OR: 1.75, 95%CI: 1.19–2.57, and p = 0.005; CT vs. CC: OR = 0.73, 95%CI: 0.57–0.94, and p = 0.016; lower HCY: C vs. T: OR = 0.74, 95%CI: 0.57–0.95, and p = 0.02; dominant: OR = 1.75, 95%CI: 0.79–1.92, and p = 0.005). No significant differences were found in other genetic models or subgroups (p > 0.05, respectively). MAD2L1 rs1283639804 polymorphism revealed a sole genotype in the studied population. HCY is significantly associated with fetal chromosome abnormalities in younger groups (OR: 1.78, 95%CI: 1.28–2.47, and p = 0.001). Conclusion: The results implied that the polymorphism of MAD1L1 rs1801368 may become the susceptibility factor to fetal chromosome abnormalities alone or combined to lower HCY levels but not to MAD2L1 rs1283639804 polymorphism. In addition, HCY significantly affects fetal chromosomal abnormalities in younger women.